2019
DOI: 10.3389/fpubh.2019.00153
|View full text |Cite
|
Sign up to set email alerts
|

Political Orientation and Public Attributions for the Causes and Solutions of Physical Inactivity in Canada: Implications for Policy Support

Abstract: Objectives: To examine how public attributions for the causes and solutions of physical inactivity and individuals' self-identified political orientation are associated with support for different policy actions in addressing physical inactivity. Methods: A secondary data analysis was conducted with a sample of 2,044 Canadian adults. Two sets of 2 X 3 analyses of variance and post-hoc analyses were conducted to assess (1) the mean differences by the caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…There is evidence that progressive/liberals are more likely to support policies and instructions that restrict individual rights but benefit the larger group. For example, liberals were more likely to support antiterrorism measures (e.g., phone tapping) in Norway (Rykkja et al, 2011) and intrusive physical‐activity policies in Canada (Yun et al, 2019). This also applies to health behaviors.…”
Section: Current Models Of Health Behaviormentioning
confidence: 99%
“…There is evidence that progressive/liberals are more likely to support policies and instructions that restrict individual rights but benefit the larger group. For example, liberals were more likely to support antiterrorism measures (e.g., phone tapping) in Norway (Rykkja et al, 2011) and intrusive physical‐activity policies in Canada (Yun et al, 2019). This also applies to health behaviors.…”
Section: Current Models Of Health Behaviormentioning
confidence: 99%
“…This finding is curious since it contradicts the idea that personal responsibility is more stressed by those on the right side of the political spectrum. There is evidence demonstrating that conservatives are generally healthier than liberals (Chan, 2019), and engage in healthier lifestyles (Subramanian et al ., 2009; Kannan and Veazie, 2018; Chan, 2019; Yun et al ., 2019). In contrast to the negative merit criteria, the reward of past usefulness or sacrifice (e.g., honourable social actions such as those impacting other peoples' health) received residual support from respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Closely related to the work on control beliefs in the context of public-policy acceptance is whether people feel responsible for a certain problem themselves or see the responsibility as resting with others instead (e.g., the government). For example, a recent online study by Yun et al (2019) found that Canadians who attributed the causes of physical inactivity internally (vs. externally or both internally and externally) were less supportive of policies to address this problem. Similarly, Mazzocchi et al (2015) found that individuals who attributed blame for high obesity rates to external factors, such as the excessive availability of unhealthy foods, supported policies addressing such factors more.…”
Section: Support-seeking Characteristicsmentioning
confidence: 99%
“…Information about the political party behind the airport proposal mediated this effect. Also, in the domain of physical inactivity, when Yun et al (2019) examined how political affiliation affects policy support, conservatives (compared with liberals or centrists) showed less support. Importantly, the researchers found that conservatives who perceive the responsibility to solve physical inactivity as a private issue (internal attribution) showed lower support for all proposed interventions.…”
Section: Support-seeking Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation